In silico study of active compounds ADMET Profiling in Curcuma xanthorrhiza Roxb and Tamarindus indica as Tuberculosis Treatment - Sherry Aristyani; M. Irsyad Nur; Sri Widyarti; Sutiman B. Sumitro (Tropical Biopharmaca Research Center, IPB University, 2018)
Curcuma xanthorrhiza Roxb and Tamarindus indica L. have been used for a long time by Indonesia local societies as tuberculosis therapy. This study explores the active compounds of Curcuma xanthorrhiza Roxb and Tamarindus indica L that important for suppressing the survival of Mycobacterium tuberculosis and predicts the pharmacokinetics and toxicity of the compounds. stringApp of Cytoscape 3.6.0 was used for screening the compounds targeting mycobacteria proteins, then computational tools like SwissADME (http://swissadme.ch/) and admetSAR (http://lmmd.ecust.edu.cn/admetsar1/predict/) were applied for estimating absorption, distribution, metabolism, excretion, and toxicity (ADMET) of active compounds. The result has been shown that there were some active compounds could target proteins of Mycobacterium tuberculosis. According to the profiling result, these compounds had a various characteristic in gastrointestinal absorption, could pass the blood-brain barrier, and had drug-like properties. In toxicity term, the active compounds did not cause Ames toxicity.